With Dr. B. C. Roy and other chief ministers : a record upto 1962 - Chakrabarty, Saroj (Benson's, 1974)
On the politics and government of West Bengal; memoirs of a government servant, with correspondence between Jawaharlal Nehru, 1889-1964, and Bidhan Chandra Roy, 1882-1962.